Engenharia Tecidual aplicada à regeneração pulpar: Análise da influência das porosidades de um scaffold sobre a proliferação e diferenciação odontoblástica de DPSCs - Conde, Marcus Cristian Muniz (2012)
Physicochemical properties and biological applicability of materials to be used in Tissue Engineering (TE) have great interest in the development of innovations in biotechnology. In dentistry research incomes every day and clarify the possibility to implement therapies for regeneration of dental pulp in clinical practice in a short time period. Such translation will require the ability to build a pulp tissue that completely fills the root canal dentin and produce appropriate vascularization to perform the metabolic exchanges needed for human tissues. To do it, we need achieve some advances; standardization of techniques and materials, which produce completely safe results, is essential to do the translation from the lab assays to RCT in humans. Based on that, the aim of this study was to perform a systematic review of the literature to analyze the knowledge regarding the importance of the interface between stem cells and scaffolds. Thereafter, we identify some gaps of knowledge in this field, as well as the techniques that have been employed today with potential to establish the transition from laboratory research to clinical. Among the obtained results, we have detected that the scaffold s physical properties, although imperative in determining cellular behavior were, little exploited since the advent of pulp stem cells. So, we carried out a study to evaluate the influence of the pore size on the proliferation and differentiation of Dental Pulp Stem Cells (DPSCs) in vitro. In order to obtain two different pore sizes (150-250μm and 251-450μm), sodium chloride was sieved and used as the porogen-inducer. Tooth slices (1-mm thickness) were obtained from recently extracted third molars and after pulp tissue removal, scaffolds with both porogen inducer sizes were prepared using PLLA (Poly-L-lactic acid) inside the pulp chamber. DPSCs (1 x 105 cells) were seeded in the scaffolds with different porosities, in 24-well plates with specific medium. The cell proliferation was evaluated using the WST1 assay at 3, 7, 14 and 21 days intervals. Also, after 21 days of culture, the RNA of seeded cells was extracted using Trizol and RT-PCR technique was used to assess the differentiation of the DPSCs in odontoblasts, using putative odontoblast markers (DSPP, DMP1 and MEPE). RNA from fresh odontoblasts was used as a control. Cell proliferation rate was similar in both scaffolds except for the 14 days period, when the cells seeded in the scaffolds with larger porosities showed higher proliferation (p<0.05). After 21 days DPSCs seeded into the dentin slices expressed the differentiation odontoblastic markers, independently of the pore sizes. The two different pore sizes tested allowed the DPSCs proliferation and differentiation